Leprosy: clinical and epidemiological study in patients above 60 years in Espírito Santo State - Brazil - Lucia Martins Diniz; Leonardo Bezerra Maciel (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Background: Leprosy is a chronic infectious disease that is endemic in Brazil and little studied in patients over 60 years old. Objective: The aim of this study was the epidemiological and clinical description of cases of leprosy in individuals older than 60 years, notified in the State of Espírito Santo - Brazil. Methods: It was an observational, descriptive and retrospective study of leprosy patients notified between 2001 and 2011. Results: Out of 16,025 notifications, 2,510 (15.6%) were of patients over 60 years of age; the distribution among the period was egalitarian except in the last 2 years, when there was a mild reduction of cases; the average was 70 years of age (±7 years); 46% were women, being 62% of those paucibacillary cases; 1,145 (50.5%) were dark-skined people in particular among paucibacillary cases; 1,638 (72.9%) were illiterates or poorly instructed n particular among multibacillary cases (P=0.022); 59.9% patients were clinically multibacillary cases and 37.4% had positive bacilloscopy; 37.9% patients had clinical alterations on peripheral nerves, 36.7% of all the multibacillary cases were classified as grade I and 15.3% as grade in assessment of disability. Study limitations: This was a retrospective study, which used secondary data generated by physicians and notified by other professionals, whar could have enabled possible errors on original data. Conclusions: Leprosy in this age group suggests a long incubation period with reactivation of latent focus or late infection. Men were more affected, as well as the afro descendent race was statistically significant in the paucibacillary cases (P=0.000) and illiterate/poor education in multibacillary cases (P=0.022). Nearly 40% of patients had positive bacilloscopy and grade I/II disability, demonstrating a late diagnosis.